2003
DOI: 10.1063/1.1604173
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characteristics of Au and Ag Schottky contacts on n-ZnO

Abstract: Au and Ag Schottky contacts on the epiready (0001)Zn surface of bulk n-ZnO crystals show Schottky barrier heights of 0.65–0.70 eV from capacitance–voltage measurements, activation energies for reverse saturation currents of 0.3–0.4 eV and saturation current densities ranging from 10−5 A cm−2 on surfaces etched in HCl to 8×10−7 A cm−2 on solvent cleaned samples. The diode ideality factors were in the range 1.6–1.8 under all conditions. The properties of both the Au and the Ag Schottky diodes were degraded by he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
94
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(102 citation statements)
references
References 26 publications
4
94
1
1
Order By: Relevance
“…These spectra were obtained in the 30-330-K temperature range, at a reverse bias of -2.0 V, filling pulse width of 2.0 ms, and filling pulse of 0.3 V. The annealed samples and the un-annealed samples show three prominent defects, E1, E2, and E3, that have been observed in ZnO and reported before. [16][17][18][19] The 300 C Ar annealing of the ZnO samples introduces a new peak E4 300 C , as has also been reported by Ref. 20.…”
Section: Resultssupporting
confidence: 59%
“…These spectra were obtained in the 30-330-K temperature range, at a reverse bias of -2.0 V, filling pulse width of 2.0 ms, and filling pulse of 0.3 V. The annealed samples and the un-annealed samples show three prominent defects, E1, E2, and E3, that have been observed in ZnO and reported before. [16][17][18][19] The 300 C Ar annealing of the ZnO samples introduces a new peak E4 300 C , as has also been reported by Ref. 20.…”
Section: Resultssupporting
confidence: 59%
“…1 also contributes to the limitation in the accurate determination of E1. The E3 defect with activation energy (0.32 6 0.01) eV below the conduction band is possibly the same defect that was observed by Polyakov et al 21 on samples obtained from Eagle-Pitcher, Grundmann et al 6 in pulsed laser deposited ZnO, and Auret et al 19 in melt grown ZnO. Its identity has been attributed to intrinsic defects, either interstitial zinc or the oxygen vacancy V o .…”
Section: Resultsmentioning
confidence: 50%
“…Polyakov et al [55] reported that annealing of Au SCs at ∼ 100 o C is already sufficient to cause surface reactions resulting in a near surface layer with reduced electron concentration and high density of deep defects. However, the thermal stability of Ag SCs seems to be higher and these contacts withstanding up to ∼ 100 o C without degrading significantly [60].…”
Section: The State Of the Artmentioning
confidence: 99%
“…However, despite the first SC to ZnO was reported by Mead [51] already in 1965, it is still challenging to realize stable and high quality SCs. For instance, the presence of a conductive surface layer due to group III ions [53], native defects both resident in the bulk and created by the metallization [54], processing [55], adsorbates [56,57], sample orientation [58,59] and presence of surface dipoles [60], can all affect the ZnO surface and the metal-semiconductor junction performance. Similar effects can account for the wide scatter, up to ∼ 2 eV in the ZnO work function (i.e.…”
Section: The State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation